Mangrove Planting: Implementation and Application of Science Instructional Design in Elementary Education Masters Program - Reza Rachmadtullah; Wan Irham Ishak; Yusmahariz Ashraf Bin Yusmaherizam; Amirul Iman Bin Baba Ismadi; Rarasaning Satyaningsih; Cholifah Tur Rosidah; Imas Srinana Wardani; Prayogo Prayogo; Danang Prastyo; Akhmad Qomaru Zaman; Muhammad Iqbal Al Ghozali (Buletin Pengabdian Multidisiplin, 2024)
Mangrove planting has great ecological benefits, including preventing abrasion, absorbing carbon, and supporting biodiversity. However, mangrove degradation due to land conversion and lack of public awareness requires intervention in the form of ecosystem rehabilitation. This activity also integrates environmental education to increase student awareness. The purpose of this service is to integrate mangrove conservation practices in project-based learning for students, involving instructional design theories that are relevant to real environmental issues. This activity also aims to support collaboration between universities and coastal communities. The results of this service are education to increase participants' understanding of the role of mangroves and correct planting techniques, seedlings are planted according to ecological conditions, with assistance to ensure success, then observation of seedling growth, additional rehabilitation, and community empowerment to maintain the sustainability of the program. The conclusion is that mangrove planting is not only beneficial for environmental conservation but also improves community welfare through ecotourism development. This activity supports sustainable development goals while providing practical learning experiences for students.